Comment éviter le burn-out (Assemble You, 2022)
Welcome to Assemble You Audio Learning. According to a survey published by Indeed in 2021, more than half of employees suffer from burnout. In 2019, the World Health Organization (WHO) officially recognized that there is a link between burnout and professional activity. Symptoms of burnout are emotional exhaustion, cynicism and inefficiency. It has been proven that people who suffer from burnout are at an increased risk of developing cardiovascular diseases, depression and anxiety. The aim of this module is to explain the mechanisms of burnout and to provide practical advice that will help you to relieve its effects. Learning objectives Learn what burnout is and what causes it Learn practical techniques to limit the negative effects of burnout or even to prevent it from occurring.